Gold (London : Financial i Production, 1988)
This video consists of four videos. The videos contents are historical importance of gold, supply, production, fabrication demand, coins, the physical market, futures and options, a monetary instrument, investment and the gold shares
Four videos in one container + one book of trainer's guide
Sponsored by Consolidated Gold Fields PLC
Copy available in DVD format
Writer, Nigel Griffiths
Keywords: Gold; Gold -- Analysis; Money market; Coinage